Microtubule Cytoskeleton Remodeling by Nanosecond Pulsed Electric Fields - Chafai, Djamel Eddine; Vostárek, František; Dráberová, Eduarda; Havelka, Daniel; Arnaud-Cormos, Delia; Leveque, Philippe; Janáček, Jiří; Kubínová, Lucie; Cifra, Michal; Dráber, Pavel (Advanced biosystems, 2020)
Remodeling of nanoscopic structures is not just crucial for cell biology, but it is also at the core of bioinspired materials. While the microtubule cytoskeleton in cells undergoes fast adaptation, adaptive materials still face this remodeling challenge. Moreover, the guided reorganization of the microtubule network and the correction of its abnormalities is still a major aim. This work reports new findings for externally triggered microtubule network remodeling by nanosecond electropulses (nsEPs). At first, a wide range of nsEP parameters, applied in a low conductivity buffer, is explored to find out the minimal nsEP dosage needed to disturb microtubules in various cell types. The time course of apoptosis and microtubule recovery in the culture medium is thereafter assessed. Application of nsEPs to cells in culture media result in modulation of microtubule binding properties to end-binding (EB1) protein, quantified by newly developed image processing techniques. The microtubules in nsEP-treated cells in the culture medium have longer EB1 comets but their density is lower than that of the control. The nsEP treatment represents a strategy for microtubule remodeling-based nano-biotechnological applications, such as engineering of self-healing materials, and as a manipulation tool for the evaluation of microtubule remodeling mechanisms during various biological processes in health and disease.
Keywords: elektřina; Humans; Microtubules; lidé; mikrotubuly; Cell Line, Tumor; nádorové buněčné linie; Electricity